Comparison of high gamma electrocorticography and fMRI with electrocortical stimulation for localization of somatosensory and language cortex. Issue 1 (January 2015) - Genetti, M.; Tyrand, R.; Grouiller, F.; Lascano, A.M.; Vulliemoz, S.; Spinelli, L.; Seeck, M.; Schaller, K.; Michel, C.M.
Highlights Stimulation of the thumb and auditory semantic decision task were used in intracranial ECoG and fMRI. The combination of hgECoG and fMRI increased the rate of patients with presurgical mapping results. The contribution of parallel localization tools can make presurgical mapping more flexible.